The role of electronic governance in developing the work of government and private banks - Assistant teacher Ali Rajab Abdel Halim (مجلة الدراسات الاقتصادية والادارية)
The The research aims to know the extent of the application of electronic governance in the two banks of Mesopotamia and Baghdad, and to know the extent of developing the work of the two banks of Mesopotamia and Baghdad, as well as knowing the impact of electronic governance in developing the work of the two banks of Mesopotamia and Baghdad The duration of the research was (14) days, as (50) questionnaires were distributed to workers in the Rafidain and Baghdad Banks, the research sample, and (40) questionnaires were retrieved. In addition, a set of statistical methods were used, represented by the arithmetic mean, standard deviation, simple correlation coefficient, and multiple regression coefficient, to test hypotheses. The research reached a set of results, namely the necessity of applying electronic governance in the Rafidain and Baghdad banks through the use of electronic financial tools in dealing with customers, including electronic payment cards, electronic transfers, and others The results also concluded that Al-Rafidain and Baghdad Banks are working to develop their operations by working to achieve the highest levels of efficiency in proportion to the planned goals. Through the questionnaire that was conducted with employees of the two banks above, the important impact of electronic governance in developing the work of Al-Rafidain and Baghdad Banks in all areas was revealed. Administrative and fiduciary fields. The research came out with a set of recommendations, including the need to pay attention to employees and try to identify their problems, listen to their opinions, and solve them because employees are an essential element in the success of any organization.